PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP PENGUKURAN KINERJA MANAJERIAL PERUSAHAAN PADA PDAM KABUPATEN KLATEN - Whidhiastuti, Vera Tri; Setyawanti, Dandang; Nursito, Sarwono (KIAT BISNIS, 2016)
The research is aimed to reveal Good Corporate Governance implementation at PDAM Klaten. It considered as qualitative reserach by distributing quessionare to employees of PDAM Klaten. The research shows Good Corporate Governance general implementation that covers transparancy, accountability, responsibility, indepndency, and fairness at PDAM Klaten is well implemented. Based on the research and data analysis with simple linear regretion analysis resulted 0.000 probability value. The values showed that Good Corporate Governance implementation take effect on managerial performance. Therefore, it can be concluded that hypothesis of âThere is an infuence of GCG over Companyâs Managerial Performance at PDAM Klatenâ, was proven and it can be accepted, which means that the implementation of Good Corporate Governance will influence managerial performance at PDAM Klaten. Keywords : Good Corporate Governance (GCG) and Managerial Performance.